Genomic assay reveals tolerance of DNA damage by both translesion DNA synthesis and homology-dependent repair in mammalian cells - Izhar, Lior; Ziv, Omer; Cohen, Isadora S; Geacintov, Nicholas E; Livneh, Zvi (Proceedings of the National Academy of Sciences - PNAS, 2013)
DNA lesions can block replication forks and lead to the formation of single-stranded gaps. These replication complications are mitigated by DNA damage tolerance mechanisms, which prevent deleterious outcomes such as cell death, genomic instability, and carcinogenesis. The two main tolerance strategies are translesion DNA synthesis (TLS), in which low-fidelity DNA polymerases bypass the blocking lesion, and homology-dependent repair (HDR; postreplication repair), which is based on the homologous sister chromatid. Here we describe a unique high-resolution method for the simultaneous analysis of TLS and HDR across defined DNA lesions in mammalian genomes. The method is based on insertion of plasmids carrying defined site-specific DNA lesions into mammalian chromosomes, using phage integrase-mediated integration. Using this method we show that mammalian cells use HDR to tolerate DNA damage in their genome. Moreover, analysis of the tolerance of the UV light-induced 6-4 photoproduct, the tobacco smoke-induced benzo[a]pyrene-guanine adduct, and an artificial trimethylene insert shows that each of these three lesions is tolerated by both TLS and HDR. We also determined the specificity of nucleotide insertion opposite these lesions during TLS in human genomes. This unique method will be useful in elucidating the mechanism of DNA damage tolerance in mammalian chromosomes and their connection to pathological processes such as carcinogenesis.